The auditory-evoked N2 and P3 components in the stop-signal task: Indices of inhibition, response-conflict or error-detection? - Dimoska, Aneta; Johnstone, Stuart J.; Barry, Robert J. (Brain and cognition, 2006)
The N2 and P3 components have been separately associated with response inhibition in the stop-signal task, and more recently, the N2 has been implicated in the detection of response-conflict. To isolate response inhibition activity from early sensory processing, the present study compared processing of the stop-signal with that of a task-irrelevant tone, which subjects were instructed to ignore. Stop-signals elicited a larger N2 on failed-stop trials and a larger P3 on successful-stop trials, relative to ignore-signal trials, likely reflecting activity related to failed and successful stopping, respectively. ERPs between fast and slow reaction-time (RT) groups were also examined as it was hypothesised that greater inhibitory activation to stop faster responses would manifest in the component reflecting this process. Successful-stop P3 showed the anticipated effect (globally larger amplitude in the fast than slow RT group), supporting its association with the stopping of an ongoing response. In contrast, N2 was larger in the slow than fast RT group, and in contrast to the predictions of the response-conflict hypothesis, successful-stop N2 and the response-locked error-negativity (Ne) differed in scalp distribution. These findings indicate that the successful-stop N2 may be better explained as a deliberate form of response control or selection, which the slow RT group employed as a means of increasing the likelihood of a successful-stop. Finally, a comparison of stimulus and response-locked ERPs revealed that the failed-stop N2 and P3 appeared to reflect error-related activity, best observed in the response-locked Ne and error-positivity (Pe). Together these findings indicate that the successful-stop N2 and P3 reflect functionally distinct aspects of response control that are dependent upon performance strategies, while failed-stop N2 and P3 reflect error-related activity.